Pengaruh Tingkat Pengungkapan Corporate Social Responsibility (CSR) Terhadap Asimetri Informasi pada Perusahaan yang Bergerak di Sektor Pertambangan dan Barang Konsumsi - Florencia Irena Chandra; Juniarti Juniarti Juniarti (Business Accounting Review, 2017)
Research on the influence of Corporate Social Responsibility (CSR) to the asymmetry of information is still rarely studied, there are only 13 research journals. However, researches on the affect of CSR on financial performance were studied more previously. This study aimed to investigate the negative influence between the level of CSR disclosure and information asymmetry, as measured by the bid-ask spread in companies engaged in mining and consumer goods. CSR disclosure level measured by using the criteria of GRI Index of 3.1, while the information asymmetry measured by using the bid-ask spread. There were two control variables used in this study, namely the predictability of earnings and the proportion of independent commissioners. The research was conducted on companies engaged in mining and consumer goods in Indonesia from 2008 to 2015 with a sample of 50 companies. The results showed that the Corporate Social Responsibility negatively affected on information asymmetry. The control variables predictability of earnings negatively affect the asymmetry of information while the proportion of independent directors did not affect the information asymmetry.